Trade Facilitation and Economic Development : Measuring the Impact - Wilson, John S.; Mann, Catherine L.; Otsuki, Tsunehiro (World Bank, Washington, DC, 2014)
The authors analyze the relationship between trade facilitation, trade flows, and GDP per capita in the Asia-Pacific region for the goods sector. They define and measure trade facilitation using four broad indicators. These are constructed using country-specific data for port efficiency, customs environment, regulatory environment, and electronic-business usage. They estimate the relationship between these indicators and trade flows using a gravity model. The model includes tariffs and other standard variables. The authors find that enhanced port efficiency has a large and positive effect on trade. Regulatory barriers deter trade. The results also suggest that improvements in customs and greater electronic-business use significantly expands trade, but to a lesser degree than the effect of ports or regulations. The authors then estimate the benefits of specific trade facilitation efforts by quantifying differential improvement by members of the Asia Pacific Economic Cooperation (APEC) in these four areas. Based on a scenario in which APEC members below average improve capacity halfway to the average for all members, the authors find that intra-APEC trade could increase by $254 billion. This represents approximately a 21 percent increase in intra-APEC trade flows, about half coming from improved port efficiencies in the region. Using Dollar and Kraay's estimate of the effect of trade on per capita GDP, these improvements in trade facilitation suggest an increase in APEC average per capita GDP of 4.3 percent.